COMPLIANCE LEVEL ANALYSIS OF COVID-19 HEALTH PROTOCOL AMONG KARANG TARUNA MEMBERS AT PANDANLANDUNG VILLAGE, MALANG - Hartati Eko Wardani; Tika Dwi Tama; Rara Warih Gayatri; Putri Djamilah Wahidah (The Indonesian Journal of Public Health, 2023)
Introduction: One of the keys to success in efforts to overcome the COVID-19 pandemic is to comply with health protocols. The COVID-19 health protocol compliance level is known to be low in the adolescent age group. The low level of compliance is related to the role of Karang Taruna as a village-level organization in providing education and examples to their peers, namely adolescents. Aims: This study was conducted to describe the level of compliance of Karang Taruna members in Pandanlandung Village, Wagir District, Malang Regency to the COVID-19 Health Protocol. Methods: The design used in this research is cross sectional with a quantitative descriptive method. This research was conducted in March-October 2021 with the number of respondents as many as 24 members of the Karang Taruna Pandanlandung Village who were selected using a total sampling technique. Results: This research study found that the compliance level of members of the Karang Taruna Pandanlandung Village was in the "Good" category, especially in the aspects of "Using Masks" 70.83%, "Washing Hands" 79.17%, "Avoiding Crowds" 50% and "Limiting Mobility" 50%. Conclusion: from this study is that, in general, the implementation of the COVID-19 health protocol is good, but the implementation of health protocols in daily life must still be improved by reminding fellow members of Karang Taruna to continue to carry out the health protocol because the pandemic is not over so as to reduce the transmission rate of COVID-19.